2020
DOI: 10.3390/membranes10090207
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Preparation and Properties of Talcum-Fly Ash Based Ceramic Membrane Supports

Abstract: Ceramic membrane method for moisture recovery from flue gas of thermal power plants is of considerable interest due to its excellent selection performance and corrosion resistance. However, manufacturing costs of commercial ceramic membranes are still relatively expensive, which promotes the development of new methods for preparing low-cost ceramic membranes. In this study, a method for the preparation of porous ceramic membrane supports is proposed. Low-cost fly ash from power plants is the main material of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Compared with the literature [ 33 , 34 ], the cooling medium is negative pressure air in this paper. When the flue gas temperature increases, the moisture content and water vapor partial pressure increase exponentially in the wet saturated flue gas [ 18 , 26 , 38 ]. The condensation process on the membrane module shell side, the transport process across the membrane and the evaporation process on the membrane module tube side are all enhanced; thus, the water recovery rate increase.…”
Section: Results and Discussmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the literature [ 33 , 34 ], the cooling medium is negative pressure air in this paper. When the flue gas temperature increases, the moisture content and water vapor partial pressure increase exponentially in the wet saturated flue gas [ 18 , 26 , 38 ]. The condensation process on the membrane module shell side, the transport process across the membrane and the evaporation process on the membrane module tube side are all enhanced; thus, the water recovery rate increase.…”
Section: Results and Discussmentioning
confidence: 99%
“…In previous studies [ 24 , 25 , 26 , 27 , 28 ], this research group also used circulating water as the cooling medium for water and waste heat recovery by ceramic membrane condenser. Figure 2 a shows the water and waste heat recovery application system under the full flue gas volume of a coal-fired power plant.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are many suggestions and recommendations reported by the scientific communities for effective utilization of fly ash for various applications. CFA has a high quantity of alumina as well as silica which are the key substances to strengthen the physical properties (chemical and mechanical resistance) of ceramic membranes during thermal treatment (Cheng et al, 2020;Fang et al, 2011;Liu et al, 2016;Usmani & Kumar, 2016;Wei et al, 2016). Dong et al (2010) prepared a disk-type low-cost ceramic membrane using coal with titania via uniaxial technique at 1300 • C. Wei et al (2016) andSuresh et al (2016) have elaborately reported on the synthesis of ceramic membranes from CFA with organic binders using polyvinyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…The research team also did a lot of research work in the early stage, ,,,,,,, and carried out a pilot test for the water and waste heat recovery from the flue gas in a 330 MW coal-fired power plant. The pilot test achieved a good effect of flue gas dehydration.…”
Section: Introductionmentioning
confidence: 99%